Delisting the Grizzly bear from the Endangered Species Act: shifting politics and political discourse in the Greater Yellowstone Ecosystem - Mollett, Sofia; Wheeler, Iree; Asay, Brandon; Holbrook, Joseph; Furland, Tommy; Manire, Hannah; Miranda Paez, Andrea; Scearce, Steelle S.; Spoonhunter, Tarissa; Stoellinger, Temple; Willoughby, Janna R.; Dunning, Kelly H. (Frontiers in Conservation Science, 2025)
IntroductionAs the Endangered Species Act (ESA) marks its 50th anniversary, it remains one of the most influential wildlife conservation laws globally. Designed to protect endangered species and their habitats, the ESA sets recovery benchmarks, with the ultimate goal of delisting species once these criteria are met. However, delisting has become a politically charged issue in recent decades, offering a critical case study for the long-term efficacy of the ESA. Our manuscript examines this dynamic through the lens of a high-profile case: the grizzly bear (Ursus arctos horribilis) in the Intermountain West region of the United States. We explore the complex process of species delisting, with research questions focusing on the political actors involved in grizzly bear delisting and their perspectives on the process.Materials and methodsTo address these questions, we analyzed 752 policy documents, news articles, and court rulings, extracting 2,832 quotes from key political stakeholders. Using a structural topic model and inductive thematic coding.ResultsWe identified five key threads of political discourse surrounding grizzly bear delisting: scientific uncertainty, the role of regulated hunting, human-wildlife conflict, increased state-level management, and the surpassing of recovery goals. Our analysis also highlights which political actors most commonly advance these arguments and how their roles have shifted over time. Notably, elected legislators, legal advocates, and non-governmental organizations are increasingly influential in wildlife policy, overshadowing the traditional authority of executive branch officials and agency scientists.Conclusions and recommendationsThese findings underscore the importance of understanding political discourse and actor dynamics in addressing ESA policy disputes, offering insights into how the law may continue to evolve and how future conflicts might be resolved.